Effect of stress unloading rate on fine-scale deformation mechanism of rock under high osmotic pressure - Sun, Weiji; Qin, Xu; Liu, Qiang; Zhang, Yujun; Ma, Wenfei; Ma, Yangqi; Gao, Jingang (Frontiers in Earth Science, 2024)
To explore the influence of the working face excavation rate on the rock deformation mechanism and seepage characteristics, deformation and seepage tests of sandstone under different loading and unloading stress paths, such as constant axial pressure unloading confining pressure and loading axial pressure unloading confining pressure, were carried out. Particle Flow Code in 3 Dimensions (PFC 3D ) and Python were used to realize fluid-solid coupling, and numerical simulation calculations were performed along the test path to analyze the influence of the unloading rate on the fine-scale deformation mechanism and permeability characteristics of sandstone, and the relationship between crack type and permeability was obtained. A sandstone fracture mechanics model is established to analyze the stress concentration degree at the end of the branch crack of the test path. The results show that the rate of confining pressure unloading is inversely proportional to the strain. Additionally, permeability correlates with the principal stress difference in an exponential manner. Interestingly, the sensitivity of permeability to stress shows an inverse trend with the unloading rate of confining pressure. Furthermore, there exists a linear relationship between permeability and the number of cracks. During the unloading process, tensile cracks predominate, and the propagation of shear cracks lags behind that of tensile cracks. The proportion of tensile cracks decreases with the increase of the unloading rate when the axial pressure is unchanged but increases when axial pressure is added, resulting in axial compression deformation and expansion deformation along the unloading direction. These research outcomes offer theoretical insights for the prudent selection of mining rates, and they hold significant implications for mitigating water inrush disasters in deep mining operations.